Clan Masdar in Local Political Contestation (Social-Political Capital Role in Political Marketing) - Sadar Bahtiar; Titin Purwaningsih (Journal of Governance and Public Policy, 2019)
Local elite competition occurs in many regions in Indonesia. One of them was in West Sulawesi, which was issued by three clans, the Manggranian Clan, the Mengga Clan, and the Masdar Clan. At present, the competition between the Mengga Clan and the Masdar Clan continues. Several political contestations in West Sulawesi have followed by-elections, both governor and regent elections. In the 2012 gubernatorial election, the Masdar Clan was defeated by Aladin S. Mengga (the Mengga Clan) and in the 2017 gubernatorial election, the Masdar Clan could win his victory. This article discusses the role of the Masdar clan socio-political capital in political marketing strategies using qualitative research methods, this study shows the socio-political capital used by the Masdar Clan is related effectively in political marketing activities. Social capital consists of bureaucracy, public trust and characterization carried out in activities through marketing. Political capital in the form of political party support/coalition, representative pairs, political experience, and successful team support is carried out in push marketing and pull marketing activities. Overall, socio-political capital is capital that is superior to the Masdar Clan. However, if examined closely, then social capital "figure" is the most decisive, the capital can make another capital.